Sex and Age Differences in Motion Sickness in Rats: The Correlation with Blood Hormone Responses and Neuronal Activation in the Vestibular and Autonomic Nuclei - Zhou, Wei; Wang, Junqin; Pan, Leilei; Qi, Ruirui; Liu, Peng; Liu, Jiluo; Cai, Yiling (Frontiers in Aging Neuroscience, 2017)
Many studies have demonstrated sex and age differences in motion sickness, but the underlying physiological basis is still in controversy. In the present study, we tried to investigate the potential correlates of endocrine and/or neuronal activity with sex and age differences in rats with motion sickness. LiCl-induced nausea symptom was evaluated by conditioned gaping. Motion sickness was assessed by measurement of autonomic responses (i.e. conditioned gaping and defecation responses), motor impairments (i.e. hypoactivity and balance disturbance) after Ferris wheel-like rotation, and blood hormone levels and central Fos protein expression was also observed. We found that rotation-induced conditioned gaping, defecation responses and motor disorders were significantly attenuated in middle-aged animals (13 and 14 month-age) compared with adolescents (1 and 2 month-age) and young-adults (4 and/or 5 month-age). LiCl-induced conditioned gapings were also decreased with age, but the was less pronouced than rotation-induced ones. Females showed greater responses in defecation and spontaneous locomotor activity during adolescents and/or young-adult period. Blood adrenocorticotropic hormone and corticosterone significantly increased in 4-months old males after rotation compared with static controls. No significant effect of rotation was observed in norepinephrine, epinephrine, β-endorphin and arginine-vasopressin levels. The middle-aged animals (13 month-age) also had higher number of rotation-induced Fos-labelled neurons in the spinal vestibular nucleus (SpVN), the parabrachial nucleus (PBN), the central and medial nucleus of amygdala (CeA and MeA) compared with adolescents (1 month-age) and young-adults (4 month-age) and in the nucleus of solitary tract (NTS) compared with adolescents (1 month-age). Sex difference in rotation-induced Fos-labelling was observed in the PBN, the NTS, the locus ceruleus and the paraventricular hypothalamus nucleus at 4 and/or 13 months of age. These results suggested that the sex and age differences in motion sickness may not correlate with stress hormone responses and habituation. The age-dependent decline in motion sickness susceptibility might be mainly attributed to the neuronal activity changes in vestibulo-autonomic pathways contributing to homeostasis regulation during motion sickness.